2002
DOI: 10.1073/pnas.162362999
|View full text |Cite
|
Sign up to set email alerts
|

An anti-transferrin receptor-avidin fusion protein exhibits both strong proapoptotic activity and the ability to deliver various molecules into cancer cells

Abstract: We have developed an antibody fusion protein (anti-rat TfR IgG3-Av) with the ability to deliver different molecules into cancer cells. It consists of avidin genetically fused to the CH3 region of a human IgG3 specific for the rat transferrin receptor. It forms strong, noncovalent interactions with biotinylated molecules such as glucose oxidase and ␤-galactosidase, and delivers them into the rat myeloma cell line Y3-Ag1.2.3 through receptor-mediated endocytosis. Importantly, the ␤-galactosidase retains activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
120
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 41 publications
(38 reference statements)
2
120
0
1
Order By: Relevance
“…It was recently shown that a nonblocking antirat TfR engineered with avidin (anti-TfR-Av) also triggers TfR endocytosis, inhibits cell proliferation, and induces apoptosis against myeloma cell line Y3-Ag1.2.3 and rat T-cell lymphoma cell line C58 (NT) D1.G.OVAR.1 cells, but only when aggregated. 25 Interestingly, A24 did not require aggregation to induce apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was recently shown that a nonblocking antirat TfR engineered with avidin (anti-TfR-Av) also triggers TfR endocytosis, inhibits cell proliferation, and induces apoptosis against myeloma cell line Y3-Ag1.2.3 and rat T-cell lymphoma cell line C58 (NT) D1.G.OVAR.1 cells, but only when aggregated. 25 Interestingly, A24 did not require aggregation to induce apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25] It has been shown that neutralizing anti-TfR antibodies can block the interaction between transferrin and TfR, and consequently iron uptake, leading to iron deprivation and negative regulation of cell growth. In this work, we have investigated the level of expression of TfR in tumor cells from acute and chronic ATL forms and the in vitro impact of a new neutralizing anti-TfR monoclonal antibody (mAb), A24, 26 on cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells of mammals such as human, mouse, rat, and Chinese hamster serve as hosts for the expression of fusion proteins of biotin-binding proteins and antibodies or other pharmaceutical proteins. [11][12][13][14][15][16][17][18] Given that the codon preferences among these mammals are similar, there is a good chance that mam-tam2A and mam-tam2B would also be highly expressed in the cells of these other mammals. One or two amino acids of mam-tam2A and mam-tam2B could be changed to create derivatives with a lower isoelectric point, 7) reversible biotin-binding capability, 8) or extremely high thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the fusion proteins were expressed in mammalian cells so that the characteristics of the fusion partners, which are quite often mammalian proteins, would be fully retained. [11][12][13][14][15][16][17][18] Monoclonal antibodies against targets such as receptors and surface proteins of cancer cells are popular fusion partners, because these fusion proteins can attach to the cancer cells to deliver the biotinylated therapeutics.…”
mentioning
confidence: 99%